Indonesian Language Curriculum Design for Foreign Learners: Business-Focused BIPA Program at the Intermediate Level, Universitas Negeri Surabaya - Octo Dendy Andriyanto; Hespi Septiana; Asrori Asrori; Dadang Rhubido; Meilita Hardika; Pensri Panich (AL-ISHLAH: Jurnal Pendidikan, 2024)
BIPA (Bahasa Indonesia bagi Penutur Asing) plays a vital role in equipping foreign learners with business-focused language skills, such as email writing, presentations, meetings, and negotiations. Tailoring the curriculum to meet business learners’ specific needs is essential for achieving practical communication proficiency. This qualitative study analyzed the needs and design of an intermediate-level BIPA curriculum for business purposes at Universitas Negeri Surabaya. Data were collected through questionnaires, observations, focus group discussions, and structured interviews with seven students from the Darmasiswa, KNB, and regular programs, and 12 BIPA instructors. The study found that 87.5% of BIPA learners had no prior exposure to business-oriented BIPA, yet there was unanimous agreement on the need for such a curriculum. Insights from surveys and interviews highlighted the importance of topics such as job applications, business communication, economics and trade, establishing cooperation, and negotiations. The findings underscore the demand for a tailored BIPA business curriculum to address learners’ professional needs. The proposed curriculum integrates relevant business communication scenarios to enhance learners’ practical language skills. Developing a business-oriented BIPA curriculum at the intermediate level is critical to meeting the growing interest and professional needs of learners at Universitas Negeri Surabaya. Future curricula should focus on practical applications to maximize learning outcomes and workplace relevance.